2013
DOI: 10.1007/s10815-013-0027-9
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease (USP26) gene alterations associated with male infertility and recurrent pregnancy loss (RPL) in Iranian infertile patients

Abstract: Background and purpose The human X chromosome is enriched with testis-specific genes that may be crucial for male fertility. Mutations in USP26 gene have been proposed to be associated with male infertility. Moreover, the importance of the ubiquitin pathway during different stages of mammalian fertilization and even embryo development has been addressed. Some mutations and haplotypes on this gene have been proposed to be associated with male infertility. In this study, five different mutations on USP26 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 49 publications
0
32
0
1
Order By: Relevance
“…Other members of the Ubiquitin-specific peptidase family have in fact been associated with male infertility and also RPL26.…”
Section: Resultsmentioning
confidence: 99%
“…Other members of the Ubiquitin-specific peptidase family have in fact been associated with male infertility and also RPL26.…”
Section: Resultsmentioning
confidence: 99%
“…Major groups of single gene defects that have been associated with pregnancy loss encompass musculoskeletal gene mutations including trinucleotide repeat disorders, genes involved in regulation of the immune system and implantation, thrombophilic gene mutations, and mutations in specific enzymes, including angiotensin-converting enzyme, ubiquitin-specific protease, and human alkaline phosphatase (Yang et al 2012a;Asadpor et al 2013;Wang et al 2013;Vatin et al 2014).…”
Section: Single Gene Defectsmentioning
confidence: 99%
“…12 Prior mutation screening has demonstrated that several USP26 gene variations were associated with male infertility, yet few functional studies have been performed. [13][14][15][16] No causative mutation in USP26 has been confirmed in infertile men.…”
Section: Introductionmentioning
confidence: 99%